Analysis on Developer’s Satisfaction Towards The Building Permit (IMB) Service Provide by The Building Service of Banjarbaru Municipality - Candra Yuliana (Universitas Lambung Mangkurat, 2006)
The Building Service Department of Banjarbaru is a technical dines service with an authority in giving IMB service where good public service is a must. Community satisfaction is a key factor to success of every institution in serving the community. Customer Satisfaction Survey is a part of research method used to know the need, demand and hope of the service user as feedbacks in improving and increasing the service quality.The goal of this research is to know the level of interested and satisfaction of the IMB service user in order to identify the attributes that must be prioritized in improving the IMB service.The research is conducted by distributing questionnaires to developer applying IMB at the Building Service of Banjarbaru, followed by validity test and data reliability test, including the descriptive and quadrant analysis (Cartesian Diagram).The result of this research shows that the average level of interest of IMB service attributes = 4.20, whereas the average valuation on the performance of IMB service = 3.36 of scale 5. It means that the performance in providing IMB service is still below the satisfaction level of the respondent (developers). The main priority of the service that must be improved according to this survey is the availability of the IMB services flowchart, ability of giving maximum service to the applicants, punctuality, the similarity in giving the service, ability in handling the complaints, service speed, commitments of the officials in providing prime service and responsibility in providing the service.